Cyclonic Mesoscale Eddy Impact on Zooplankton Vertical Migration at Station ALOHA in the Coast of Hawaii - Engida, Kelebet (My University, 2021)
Light intensity over the course of a day sets the circadian rhythm for the vertical movement of microorganisms across the entire ocean. This research focused on the distribution of zooplankton at station ALOHA off the coast of Hawaii and examines the influence of cyclonic eddies on the vertical migration of zooplankton. I hypothesize that eddies increase vertical migration of zooplankton abundance. The null as evidenced by changes in zooplankton dry weight with depth was there would be no increase in the overall dry weight biomass when eddies pass through the station. Eddies that pass over station ALOHA were identified from satellite altimetry based on sea surface height anomalies. Hawaii ocean time series cruise data was used to determine the distribution of the zooplanktons at this station. The zooplankton data covered 1994-2017, nearly a 26year time series. Zooplankton dry weight in (g.m^2) was used to estimate the abundance of zooplankton at three different depth with a maximum depth of 175m. This paper aims to answer at what depth is there a significant difference in Zooplankton distribution during day and night? If there is a difference, how does the presence of eddies impact the distribution of zooplankton? The influence of eddies was compared to without the influence of eddies at the respective depth. Eddies properties like age, amplitude, velocity, radius, and polarity were all compared with zooplankton distribution in the absence of eddies to understand if there was a statistically significant difference in the influence of eddies. There were two findings in this paper. (1) The zooplankton distribution was significantly different between the depth of 75-175m. (2) Radius, Polarity, Amplitude, and age of eddies had significant impact on the vertical migration of zooplankton.
Keywords: Zooplankton; Station ALOHA; Hawaii; Diel vertical migration; Eddies